IMPLEMENTASI ETIKA KOMUNIKASI ISLAM DALAM INTERAKSI SOSIAL MUSLIM DAN NON-MUSLIM DI KABUPATEN KARO - Zulham, Zulham; Abdullah, Abdullah (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to analyze the application of Islamic communication ethics in social interaction between Muslims and Non-Muslims in Karo Regency, which is known as an area with significant religious diversity in Indonesia. The main focus of this study is to explore how the ethical principles of Islamic communication are implemented in everyday social life, particularly in an effort to create harmony and prevent conflicts. The methodology used in this study is a qualitative approach, which includes in-depth interview techniques, observation, and document analysis. The findings of this study indicate that values such as qaulan ma'rufan (good words), qaulan kariman (noble words), and qaulan layyinan (gentle words) are applied in interactions both between individuals and between communities. The application of these values contributes to an increase in mutual respect, tolerance, and empathy among Muslims and Non-Muslims. However, this study also identifies challenges in the application of communication ethics, such as the emergence of interreligious stereotypes and prejudices that are often caused by cultural differences and religious understanding. The conclusion of this study confirms that the consistent application of Islamic communication ethics can be a crucial foundation in maintaining social cohesion in a multicultural society. The recommendations of this study include the importance of intercultural education and more intensive interfaith dialogue to strengthen social harmony.